Maritime Minded Learning through Singing Media at Al Qaariah Kindergarten Muna Regency - Erna Budiarti; Masnah, Masnah (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2024)
This study aims to investigate the effectiveness of maritime-oriented learning through singing at Al Qaariah Kindergarten, Renda Village, Towea District, Muna Regency. Singing was chosen as a learning method to integrate maritime concepts into the early childhood education curriculum. This research used a qualitative approach with a case study research design. The research participants consisted of 30 young children at Al Qaariah Kindergarten. Data were collected through classroom observation, interviews with teachers, and documentation analysis. The results showed that the consistent use of singing media can improve children's understanding of maritime concepts, such as marine life, maritime transportation, and the diversity of maritime culture. In addition, maritime-oriented learning through singing media also helps develop social skills, creativity and love for the marine environment. Teachers and parents gave positive responses to the implementation of this learning, noting an increase in children's enthusiasm and participation in learning activities. This research contributes to the understanding of the importance of a maritime-minded approach in early childhood learning and demonstrates that singing can be an effective tool in bringing this concept to young children in a fun and interactive way. The implications of this research can be used as a basis for the development of similar learning methods in other educational institutions that want to integrate a maritime approach in their curriculum.